A philosophy of climate apocalypticism - Kowalewski, Jakub (Lecturer in philosophy), author.
1 online resource.
Keywords: "This book offers a long-overdue analysis of the ubiquity of eco-apocalypticism in current discourses on the climate crisis. Drawing on a wide range of sources and theoretical traditions from ecological works and radical pamphlets, through political theology and continental philosophy to ancient and medieval apocalypses, the book sheds a comprehensive light on the concepts, processes, and experiences which circulate around the figure of the environmental end of the world. Importantly, this book argues that apocalypticism can provide a productive philosophical framework for addressing the climate catastrophe, enabling us to propose a distinctive answer to the fundamental question which haunts progressive ecological projects: how can we defend the world we find indefensible? Appealing to students, academics and researchers in philosophy, political theology, and environmental humanities, this book is a timely intervention which hopes to demonstrate that, when all else fails, it is the end of the world which may save the planet"--